1997
DOI: 10.1163/156853997x00610
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Aggression and Conciliation in Three Cercopithecine Monkeys (Macaca Fuscata, Macaca Nigra, Papio Papio)

Abstract: Patterns of aggression and reconciliation were studied in three captive groups of monkeys belonging to different species: Japanese macaques (Macaca fuscata), crested macaques (M. nigra) and Guinea baboons (Papio papio). Consistent differences were found comparing same dyads of individuals in the three groups. Aggression was often followed by retaliation and reconciliation in the group of crested macaques, such responses occurred less frequently in the group of Japanese macaques, more variable results were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
86
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 54 publications
7
86
0
Order By: Relevance
“…In the latter two species, conflicts are unidirectional, high-intensity aggression is common, and reconciliations are not frequent. 32,[53][54][55][56][57][58] Quantitative analyses have shown quite different patterns of aggression and response to aggression in Sulawesi macaques (Tonkean, crested, and moor macaques). A majority of their conflicts are bidirectional, and most aggressive acts induce protest or retaliation.…”
Section: Social Styles As Covariant Sets Of Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter two species, conflicts are unidirectional, high-intensity aggression is common, and reconciliations are not frequent. 32,[53][54][55][56][57][58] Quantitative analyses have shown quite different patterns of aggression and response to aggression in Sulawesi macaques (Tonkean, crested, and moor macaques). A majority of their conflicts are bidirectional, and most aggressive acts induce protest or retaliation.…”
Section: Social Styles As Covariant Sets Of Traitsmentioning
confidence: 99%
“…Measuring conciliatory tendencies yields high values, around 50% among unrelated partners (Box 2). 31,54,57,59,60 Other macaques are located intermediately between previous species regarding patterns of aggression and reconciliation. Longtailed and pigtailed macaques are most similar to rhesus and Japanese macaques, whereas stumptailed, Barbary, liontailed, and bonnet macaques are most comparable to the Sulawesi macaques.…”
Section: Social Styles As Covariant Sets Of Traitsmentioning
confidence: 99%
“…We previously showed that both species exhibit different styles of interaction (Petit, Thierry, & Abegg, 1997). In Japanese macaques, conflicts were mostly unidirectional.…”
Section: Introductionmentioning
confidence: 98%
“…In Sulawesi macaques, the relationships are influenced relatively little by social rank and kinship ties, they do not use intense submission patterns to approach each other and their overall levels of tolerance are quite high (Bernstein & Baker, 1988;Matsumura, 2001;Thierry, 2004;Thierry, Anderson, Demaria, Desportes, & Petit, 1994). In particular, rates of counter-aggression among adults were higher in Japanese macaques than in crested macaques (Petit et al, 1997). Conversely, reconciliatory tendencies were lower in the former than in the latter (Petit et al, 1997;Thierry et al, in press; see also Bernstein, Williams, &Ramsay, 1983, andChaffin et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…In this case, affiliative interactions can arise more easily between opponents. Aggression intensity, dominance asymmetry and affiliation rates after conflicts can therefore be considered to belong to the same system of interrelated traits (Petit et al 1997;Thierry 2007). The occurrence of coalitions most probably creates a positive feedback loop between levels of dominance asymmetry and nepotism.…”
mentioning
confidence: 99%